La contaminación de los recursos hídricos del cantón Riobamba y la vulneración de los derechos de sus habitantes y de la naturaleza. - Heredia Montes, Sofía Monserrath (2022)
The present investigation entitled "THE POLLUTION OF THE WATER RESOURCES OF THE RIOBAMBA CANTON AND THE VIOLATION OF THE RIGHTS OF ITS INHABITANTS AND OF NATURE", is based on the Chibunga River, as it is one of the water resources that is affected by pollution. environmental. In this virtue, the work is directed to the study and analysis of the national, provincial and cantonal regulations that allow the mitigation of environmental contamination in the natural water source and consequently to determine the rights that are violated in this process. For these reasons, the research was structured as follows: an introduction where the most outstanding elements of the projected research plan are highlighted; three chapters: the first, containing the methodological rudiments that support the investigative work; the second, which outlines the entire theoretical framework on which the chosen topic is based, the state of the art related to environmental pollution of the aforementioned hydrographic basin and the effective exercise of the rights of the citizens of Riobamba, from that affectation; the third of the chapters, was destined to specify the methodology followed, that is, the algorithm of steps that were followed during the investigative work. Finally, the conclusions stand out, where those elements that affect the contamination of the Chibunga River and its direct connection with the adequate exercise of the rights of good living of the locals are highlighted. Criteria that rounded off the achievement of the proposed topic and the achievement of study material for those interested in the subject.